FNR-Dependent RmpA and RmpA2 Regulation of Capsule Polysaccharide Biosynthesis in Klebsiella pneumoniae - Lin, Tien-Huang; Wu, Chien-Chen; Kuo, Jong-Tar; Chu, Hsu-Feng; Lee, Ding-Yu; Lin, Ching-Ting (Frontiers in Microbiology, 2019)
Fumarate nitrate reduction regulator (FNR) is a direct oxygen-responsive transcriptional regulator containing an iron-sulfur (Fe-S) cluster. During anaerobic growth, the [4Fe-4S] cluster in FNR (holo-FNR) binds specifically to DNA, whereas exposure to oxygen results in the loss of its DNA-binding activity via oxidation of the [4Fe-4S] cluster. In this study, we aimed to investigate the role of FNR in regulation of capsular polysaccharide (CPS) biosynthesis, serum resistance, and anti-phagocytosis of K. pneumoniae. We found that the CPS amount in K. pneumoniae increased in anaerobic conditions, compared to that in aerobic conditions. An fnr deletion mutant and a site-directed mutant (fnr3CA), with the three cysteines (C20, C23, and C29) replaced with alanines to mimic an FNR lacking the [4Fe-4S] cluster, showed marked increase in CPS amount under anaerobic conditions. A promoter-reporter assay and qRT-PCR confirmed that the transcription of the cps genes was repressed by holo-FNR. In addition, we found that holo-FNR could repress the transcription of rmpA and rmpA2, encoding cps transcriptional activators. Deletion of rmpA or rmpA2 in the fnr strain reduced CPS biosynthesis, suggesting that RmpA and RmpA2 participated in the holo-FNR–mediated repression of cps transcription, thereby regulating the CPS amount, serum resistance, and anti-phagocytosis. Taken together, our results provided evidence that RmpA and RmpA2 participated in the holo-FNR–mediated repression of CPS biosynthesis, and resistance to the host defense in response to oxygen availability.